Rethinking the Quality Culture of Indonesian Madrasa in the Global Era - Mohammad ‘Ulyan; Guntur Dwi Purwanto Guntur Dwi Purwanto; Abdul Basit Abdul Basit (International Journal of Social Science and Religion (IJSSR), 2021)
Madrasa have a big role in building the Indonesian nation. The challenges of education in the era of globalization are getting bigger. However, many madrasa do not have the quality according to the standard. Therefore it is necessary to rethink the quality culture of madrasa in the global era. This type of research is qualitative research and includes field research. Data analysis using Miles and Huberman analysis techniques that include data reduction, display data, and conclusion drawing/verification. The results of research conducted by the author on the implementation of quality culture madrasa in MTs Ma'arif NU 4 Kemranjen can be concluded that wujud from the quality culture madrasa (religious culture) in MTs Ma'arif NU 4 Kemranjen as a form of development of pai subject family in accordance with the theory that includes; (1) mushofahah (2) memorization juz 'amma (3) istighasah and prayer together (4) dhuha prayer (5) friday box running (6) congregational dhuhur prayer (7) religious message. While what is not contained in the theory is (1) PHBI (2) reading asmaul husna (3) the use of polite uniforms and covering the aurat (4) pesantren kilat (5) reading yasin and tahlil (6) extra-curricular religious (7) religious tests (8) halal bihalal. The implementation uses a persuasive strategy that emphasizes on accuracy and habituation.